Highway(s) overhead: Strong differences in wetland connectivity and protected status challenge waterbird migration along the four Palearctic‐Afrotropical flyways. (10th March 2022) - Deboelpaep, Evelien; Partoens, Lisa; Koedam, Nico; Vanschoenwinkel, Bram
Abstract: Aim: Waterbirds that travel seasonally between Europe and Africa use wetlands along four major Palearctic‐Afrotropical flyways. However, it is unknown to what extent the overall connectivity of these flyways may be threatened by ongoing habitat loss and degradation. Here, we contrasted the wetland connectivity along these four flyways, applying graph‐theoretic connectivity metrics on an intercontinental scale. We also explored for which flyway connectivity is most at risk. We then identified the most important wetlands by their contribution to connectivity in each flyway. Location: Western Palearctic, Afrotropics. Methods: Based on high‐resolution wetland maps, we calculated directional probabilistic connectivity metrics. Estimates of overall connectivity of each flyway were obtained, as well as the relative importance of wetlands, for birds with different migration strategies: short‐distance hoppers and long‐distance jumpers. Results: The East‐Atlantic flyway and Eastern Mediterranean flyway had higher overall functional connectivity than the two central routes, reflecting the larger barrier represented by the Mediterranean Sea and Sahara Desert. Fewer than 5% of all wetlands supported more than 70% of the total connectivity of the network in each flyway, regardless of the considered migration strategy. These wetlands were either large, strategically positioned or both. Removing non‐protected wetlands from the analysis showed that the connectivity of some flyways could be jeopardized and that the East‐Atlantic and Eastern Mediterranean flyway may be most vulnerable to additional habitat loss. Main conclusions: Our results illustrate (i) the major contribution of unprotected wetlands to flyway connectivity, (ii) the importance of integrating migration ecology into site‐based connectivity analyses and (iii) the utility of graph‐based connectivity metrics to inform conservation prioritization under present and future scenarios.